2011
DOI: 10.3415/vcot-11-06-0081
|View full text |Cite
|
Sign up to set email alerts
|

Influence of screw insertion order on compression generated by bone plates in a fracture model

Abstract: Present recommendations regarding order of screw insertion for compression plate osteosynthesis in veterinary training are variable. We hypothesized that placement of a neutrally positioned screw would reduce the magnitude of compression that could be generated by a subsequently placed compression screw. Canine tibial diaphyseal segments were fixed to a plate attached to a bone surrogate and load cell, and the compression generated by screw tightening was measured. Three different screw insertion order pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…A study by Jermyn and Roe investigating the influence of cortical screw insertion order on compression in a fracture model showed that compression from a load screw will be compromised by a previously placed screw. 18 The overall plate length and size may also alter the amount of displacement. The type of drill guide used could change the displacement achieved, while the use of a universal drill guide in locking compression plates instead of a standard loading DCP drill guide will lead to increased displacement.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Jermyn and Roe investigating the influence of cortical screw insertion order on compression in a fracture model showed that compression from a load screw will be compromised by a previously placed screw. 18 The overall plate length and size may also alter the amount of displacement. The type of drill guide used could change the displacement achieved, while the use of a universal drill guide in locking compression plates instead of a standard loading DCP drill guide will lead to increased displacement.…”
Section: Discussionmentioning
confidence: 99%